Risk of Preterm Delivery Associated with Prior Treatment of Cervical Precancerous Lesion according to the Depth of the Cone. Issue 6 (13th November 2013) - Berretta, Roberto; Gizzo, Salvatore; Dall'Asta, Andrea; Mazzone, Eleonora; Monica, Michela; Franchi, Laura; Peri, Francesca; Patrelli, Tito Silvio; Bacchi Modena, Alberto
Abstract : The aim of this study was to evaluate the impact of the surgical excisional procedures for cervical intraepithelial neoplasia (CIN) treatment both on subsequent fertility (cervical factor) and pregnancy complication (risk of spontaneous preterm delivery). We retrospectively analyzed 236 fertile women who underwent conization for CIN. We included in the study 47 patients who carried on pregnancy and delivered a viable fetus. Patients were asked about postconization pregnancies, obstetrical outcomes, and a possible diagnosis of secondary infertility caused by cervical stenosis. We evaluated the depth of surgical excision, the timing between cervical conization and subsequent pregnancies, surgical technique, and maternal age at delivery. We recorded 47 deliveries, 10 cases of preterm delivery; 8 of them were spontaneous. The depth of surgical excision showed a statistically significant inverse correlation with gestational age at birth. The risk of spontaneous preterm delivery increased when conization depth exceeded a cut-off value of 1.5 cm. Our data do not demonstrated a relation between conization and infertility due to cervical stenosis.